Evaluative beliefs in a thought theoretical framework?: A proposal for non-positing epistemic states - Neuber, Simone (Estetika, 2015)
Thought Theory (TT) seems to provide an answer to the paradox of fiction (PoF) which has the ontological merits of current pretence accounts without, however, assuming mere pretence emotions. This article will question whether present formulations of TT live up to what they promise. Whenever its current versions try to include evaluative beliefs in a TT framework in order to comply with a cognitivist account of emotions, they either stop being a genuine thought theory or endorse the irrationalism of fictional emotions. This unfortunate outcome can be prevented by shifting the focus to thoughts, and specifically to the genetic dynamics of how we come to think of the objects in question. This is at least what we can learn from Edmund Husserl, who developed a still underestimated account according to which it is possible to have the belief that x merits evaluation as appearing emotion-worthy without this belief implying that x merits being believed to exist.